An overview of mosquitoes and emerging arboviral infections in the Zagreb area, Croatia - Klobucar, Ana; Benic, Nikola; Krajcar, Darko; Kosanovic-Licina, Mirjana Lana; Tesic, Vanja; Merdic, Enrih; Vrucina, Ivana; Savic, Vladimir; Barbic, Ljubo; Stevanovic, Vladimir; Pem-Novosel, Iva; Vilibic-Cavlek, Tatjana (The Journal of Infection in Developing Countries, 2016)
Mosquito control in the Zagreb area has been conducted for many years, whereas the fauna has only been investigated in the last 20 years. So far 30 mosquito species have been detected in the city area. Culex pipiens form molestus is the dominant mosquito species in indoor breeding sites. In forested areas and areas exposed to flooding, the active period is early spring and the dominant species are Ochlerotatus sticticus, Ochlerotatus cantans, Ochlerotatus geniculatus and Aedes vexans. The eudominant mosquito species found in the artificial breeding sites are Culex pipiens and the Asian tiger mosquito, Aedes albopictus. Invasive Ae. albopictus, present in the Zagreb area since 2004, has expanded to a larger area of the city during the last three years. The recent emergence of the human West Nile virus and Usutu virus neuroinvasive disease in Zagreb and its surroundings highlighted the role of mosquitoes as vectors of emerging arboviruses. The paper focuses on mosquito species and arboviral infections detected in humans and animals in the Zagreb area, Croatia.